Frequency of Knee Pain and Risk Factors and Its Impact on Functional Impairment: A Cross-Sectional Study from Saudi Arabia - Ali H. Alyami; Hussam Darraj; Khalid M. Hakami; Faisal Hakami; Mohammed Awaf; Nawaf Bakri; Sulaiman Hamdi; Abdulaziz Saber; Almuhanad Alyami; Mohammed Khashab; Abdulaziz H. Alhazmi (MDPI AG, 2023)
Background: Adolescents frequently self-report pain, according to epidemiological research. The knee is one of the sites wherein pain is most commonly reported. Musculoskeletal disorders play a significant role in the prolonged disability experienced by individuals, leading to substantial global personal, societal, and economic burdens. Patellofemoral pain (PFP) is a clinical knee pain commonly affecting adolescents. This study aimed to estimate the frequency of knee pain in Saudi adolescents. Methods: This cross-sectional survey was conducted from June to November 2022 and included 676 adolescents aged 10 to 18 years. The participants were questioned regarding their demographics, school habits, and the impact of these factors on back pain, musculoskeletal pain in the past 12 months, as well as quality-of-life scale and knee pain symptoms. The data were analyzed using descriptive statistics, with frequencies and percentages presented for categorical variables. Analysis of variance (ANOVA) was performed to compare means between groups, while the chi-squared test was used to compare categorical variables. Statistical significance was set at p < 0.05. Results: A total of 676 adolescents participated in the study, with 57.5% females and 42.5% males. Among the participants, 68.8% were aged between 15 and 18 years. The prevalence of knee pain was notably higher among females (26%) compared to males (19.2%). Age and BMI were identified as significant predictors of knee pain. A significant association was also found between BMI classification and knee stiffness (p-value = 0.008). Furthermore, a significant difference was observed between adolescents who engaged in physical activities during leisure time and those who experienced difficulty bending (p-value = 0.03). Conclusions: Our study highlights a high prevalence of knee pain among Saudi adolescents, emphasizing the need for increased awareness about its risk factors. Preventive measures, including conservative approaches and lifestyle/activity modifications, can effectively mitigate adolescent knee pain.